A 0.18µm CMOS DDCCII for Portable LV-LP Filters - V. Stornelli; G. Ferri (Radioengineering, 2013)
In this paper a current mode very low voltage (LV) (1V) and low power (LP) (21 µW) differential difference second generation current conveyor (CCII) is presented. The circuit is developed by applying the current sensing technique to a fully balanced version of a differential difference amplifier (DDA) so to design a suitable LV LP integrated version of the so-called differential difference CCII (DDCCII). Post-layout results, using a 0.18µm SMIC CMOS technology, have shown good general circuit performances making the proposed circuit suitable for fully integration in battery portable systems as, for examples, fully differential Sallen-Key bandpass filter.